Evaluasi Pengaruh Aktivitas Antropogenik terhadap Populasi Ikan Bilih (Mystacoleucus padangensis) di Danau Singkarak - Esy Maestro; Faulina Salsabilla; Ridhwan Hamid; Wani Sovia; Yola Dwi Sandra (Jurnal Pengabdian Kepada Masyarakat, 2025)
The bilih fish (Mystacoleucus padangensis) is an endemic species of Lake Singkarak that holds high ecological and economic value for the surrounding community. However, in recent decades, the population of this fish has shown a significant decline. This study aims to evaluate the influence of anthropogenic activities on the population dynamics of the bilih fish in Lake Singkarak. The methods used included field surveys, interviews with local fishermen, and analysis of secondary data related to human activities such as overfishing, water pollution, infrastructure development, and changes in land use around the lake. The results indicate that the greatest pressure comes from unsustainable fishing practices, including the use of fishing gear that damages habitat and the lack of regulated fishing seasons. In addition, domestic and agricultural waste flowing into the lake causes a decline in water quality, which directly impacts the bilih fish's life cycle. Development activities, such as road construction and massive tourism, also contribute to the disruption of the lake's ecosystem. Therefore, community-based conservation measures, enforcement of fisheries regulations, and regular environmental quality monitoring are needed to maintain the sustainability of the bilih fish population in the future.